Acoustic territories sound culture and everyday life - LaBelle, Brandon 1969- (Bloomsbury Academic, 2019)
"The revised edition of Acoustic Territories: Sound Culture and Everyday Life offers an expansive reading of auditory life. It provides a careful consideration of the performative dynamics inherent to sounding and listening, and discusses how sound studies may illuminate understandings of contemporary society. Combining research on urbanism, popular culture, street life and sonic technologies, Acoustic Territories opens up a range of critical perspectives--it challenges debates surrounding noise pollution and charts an 'acoustic politics of space' by engaging auditory experience as found within particular cultural histories and related ideologies. Brandon LaBelle traces sound culture through a topographic structure: from underground territories to the home, and further, into the rhythms and vibrations of streets and neighborhoods, and finally to the sky itself as an arena of transmitted imaginaries. The new edition includes an additional 'global territory' of the relational, positioning acoustics as a range of everyday practices that rework dominant tonalities. Questions of orientation and emplacement are critically raised, reframing listening as multi-modal and intrinsic to resistant socialities and what the author terms 'acts of compositioning.' The book is fully updated to include new relevant research and references surfacing since 2010, as well as a new preface to the second edition. Acoustic Territories continues to uncover the embedded tensions and potentialities inherent to sound as it exists in the everyday spaces around us"--Bloomsbury Collections
Previous edition: New York: Continuum, 2010
Includes bibliographical references and index
Keywords: Geräuschkulisse; Soziologie; Alltagskultur; Massenmedien; Schall; Akustischer Reiz; Luftschall; Klang; Geräusch; Performance -- Künste; Performance art; Sound / Social aspects; Sound in mass media; Electronic books